Australian Politics in a Digital Age - John Chen, Peter (ANU Press, 2013)
Information and communications technologies are increasingly important in the Australian political landscape. From the adoption of new forms of electoral campaigning to the use of networking technology to organise social movements, media technology has the potential to radically change the way politics is conducted and experienced in this country. The first comprehensive volume on the impact of digital media on Australian politics, this book examines the way these technologies shape political communication, alter key public and private institutions, and serve as the new arena in which discursive and expressive political life is performed. Employing a range of theoretical perspectives, empirical data, and case examples, the book provides insights on political behaviour of Australia's elites, as well as the increasingly important politics of mirco-activism and social media. Energetic and fast-paced, the book draws together a wide range of Australian and international scholarship on the interface between communications technology and politics. Crossing several genres, the book will find a wide audience amongst scholars of both politics and communication, among public relations professionals, and with members of the media themselves.